Rancang Bangun Aplikasi Penilaian Kinerja Distributor Pupuk Bersubsidi Pada Dinas Pertanian Perkebunan Peternakan Kabupaten Sidoarjo - Ari Setyo Budiono; Vivine Nurcahyawati; Martinus Sony Erstiawan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Distributors are intermediaries between producers and consumers, distributor role is quite important in the process of distributing goods to consumer needs. Distribution process is well organized, can help develop economy. One of them is subsidized fertilizer, fertilizer production facilities is supporting farmers to determine the achievement of national self-sufficiency in agricultural production. current problems  KPPP difficulties in assessing the performance of distributors due process of calculating  indicators to distributors are not applied. Consequently monitoring the performance of distributors not inaccurate. The impact of these problems is the KPPP does not determine the development of subsidized fertilizer distribution, if  the distributor  do action fertilizer distribution irregularities. ( Permendag 15/ M-DAG/PER/4/2013 about procurement and distribution of fertilizer subsidized agricultural sector). Based on these problems, Application a  performance  assessment  distributor  use 5 indicators are legality aspect, accessibility aspect, quantity fulfillment aspect, quality fulfillment  aspect and respon  and lead time aspect. This indicators as a measure to support the fulfillment subsidized fertilizer requirement is right on target. Applications are made to produce performance assessment report, distributors quality report, and distributors level reports. Based on the application made and a series of trials that have been done KPPP can find out the information required in accordance with the purpose of performance appraisal distributor Keywords : Application, Distributors, performance assessment